Islet amyloid polypeptide: pinpointing amino acid residues linked to amyloid fibril formation. - Westermark, P (1990)
Islet amyloid polypeptide (IAPP), a putative polypeptide hormone, is a product of pancreatic beta-cells and the major constituent of the amyloid deposits seen mainly in islets of type 2 diabetic humans and diabetic cats. The connection between IAPP amyloid formation and diabetes is unknown, but a limited segment of the IAPP molecule, positions 20-29, seems responsible for the aggregation to fibrils. Differences in the amino acid sequence of this region probably determine whether or not islet amyloid can develop in a particular species. Amyloid fibril formation can be mimicked in vitro with the aid of synthetic peptides. With this technique we show that peptides corresponding to IAPP positions 20-29 of human and cat, species that develop IAPP-derived islet amyloid, form amyloid-like fibrils in vitro. The corresponding IAPP segment from three rodent species that do not develop IAPP-derived amyloid did not give rise to fibrils. Substitution of the human IAPP-(20-29) decapeptide with one or two amino acid residues from species without islet amyloid generally reduced the capacity to form fibrils. We conclude that the sequence Ala-Ile-Leu-Ser-Ser, corresponding to positions 25-29 of human IAPP, is strongly amyloidogenic and that a proline-for-serine substitution in position 28, as in several rodents, almost completely inhibits formation of amyloid fibrils.